1969
DOI: 10.12669/pjms.301.4228
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis Associated With Pneumatic Tube System Transport For Blood Samples

Abstract: Objective: The frequency of hemolysis of blood samples may be increased by transport in a pneumatic tube system. The purpose of this study was to evaluate the effect of pneumatic tube system transport on hemolysis of blood samples. Methods: Blood samples were transported from the emergency department to the hospital laboratory manually by hospital staff (49 patients) or with a pneumatic tube system (53 patients). The hemolysis index and serum chemistry studies were performed on the blood samples and compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 0 publications
1
35
0
2
Order By: Relevance
“…Recently, Kara et al [8] reported 100% of PTS-transported samples as being hemolyzed compared to only 16% of manually transported samples, completely in contrast to the nonsignificant difference between transportation methods found in a previous study [4]. Neither of these studies use paired samples for a head-to-head comparison and their conclusions pertaining to the respective danger and safety of PTSs indicates they relied on the assumption that their sample populations had identical susceptibilities to hemolysis.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, Kara et al [8] reported 100% of PTS-transported samples as being hemolyzed compared to only 16% of manually transported samples, completely in contrast to the nonsignificant difference between transportation methods found in a previous study [4]. Neither of these studies use paired samples for a head-to-head comparison and their conclusions pertaining to the respective danger and safety of PTSs indicates they relied on the assumption that their sample populations had identical susceptibilities to hemolysis.…”
Section: Discussionmentioning
confidence: 92%
“…It is equally important to validate new methodologies in the context of their realworld use to ensure they do not jeopardize that which they are ultimately designed to improve: patient care. After analyzing 48 commonly tested hematology, coagulation, chemistry and blood gas parameters, including those most likely to be affected by pneumatic tube transport [6,[8][9][10][11][12], no analytes were judged to have clinically significant differences when transported to the core laboratory via PTS versus manual courier. Hence, our PTS was validated for the transportation of samples ordered for all the included routine blood tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the reasons for high hemolysis rates are likely multifactorial, they are typically caused by the pre-analytic phase of the testing process 2. One possible source is the use of pneumatic tube transport systems to transfer the test tubes from the ED to the clinical laboratory 5,6…”
Section: Introductionmentioning
confidence: 99%
“…However, the decrease in turnaround time might come at the cost of sample quality. Ellis and Hasan both led ED-based studies that revealed significantly increased specimen hemolysis rates after pneumatic tube systems were installed 5,6. In contrast, other studies of pneumatic tube use demonstrated no significant changes in hemolysis rates 8,9,1115.…”
Section: Introductionmentioning
confidence: 99%